2020
DOI: 10.1177/0036850420921682
|View full text |Cite
|
Sign up to set email alerts
|

Selection and techno-economic analysis of hybrid ground source heat pumps used in karst regions

Abstract: In order to take advantage of different forms of heat pumps and to mitigate thermal imbalance underground caused by long-term operation of ground source heat pumps, hybrid ground source heat pump systems have received an increasing attention. In this research, based on the fact that abundant groundwater resources are commonly available in karst regions, a new strategy is introduced for selecting and determining hybrid ground source heat pump capacity. Five scenarios of hybrid ground source heat pump system cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Y. Tian et al [9] built an analytical model to study the heating performance considering the condition of groundwater seepage and the results showed that the groundwater can mitigate the decrease in soil temperature near the energy piles located upstream. W. Zhou et al [10] proposed hybrid ground source heat pumps integrating GCHP and a groundwater source heat pump to eliminate the heat imbalance problem and to reduce investment. In engineering practice, the difference in energy between heating and cooling was restricted artificially to mitigate the thermal imbalance.…”
Section: Introductionmentioning
confidence: 99%
“…Y. Tian et al [9] built an analytical model to study the heating performance considering the condition of groundwater seepage and the results showed that the groundwater can mitigate the decrease in soil temperature near the energy piles located upstream. W. Zhou et al [10] proposed hybrid ground source heat pumps integrating GCHP and a groundwater source heat pump to eliminate the heat imbalance problem and to reduce investment. In engineering practice, the difference in energy between heating and cooling was restricted artificially to mitigate the thermal imbalance.…”
Section: Introductionmentioning
confidence: 99%